Marketing and Negotiating in the People's Republic of China: Perceptions of American Businessmen Who Attended the 1975 Canton Fair - Brunner, James A.; Taoka, George M. (Journal of International Business Studies, 1977)
The objective of this study is to evaluate the various aspects of the business opportunities and peculiarities of negotiating in the People's Republic of China as viewed by businessmen who attended the recent Canton Trade Fairs. Many of the peculiarities still remain, as attested to by the respondents of the self-administered questionnaires that were mailed to 218 businessmen. However, these businessmen indicate that the Chinese are becoming more flexible in their negotiations and are sincerely interested in expanding their trade with the United States.